A Study of Factors Affecting Malaysian Customers’ Purchase Intention toward Hybrid Vehicle - Siow, Khin Shiun (2012)
The hybrid vehicles are becoming more popular in Malaysia. Although the sales of hybrid vehicles are getting increase, but the model of hybrid vehicles that draw into Malaysia’s market are still limited. Automobile manufacturers are still monitoring the sales of hybrid vehicles in order to make decision in accessing Malaysia’s hybrid vehicle’s market. Thus, it is crucial to investigate about the factors that affecting the purchase intention toward hybrid vehicle among Malaysian, especially from the perspective of potential buyers. The findings of this research would provide a deeper insight on the factors that affecting purchase intention toward hybrid vehicle among Malaysian which above 25 years old. The model of 4 A’s is included as factors in this study, where the derivation of the A’s are: availability, affordability, accessibility and awareness. Based on the research finding from 186 respondents, three (3) factors from the model shows significant in affecting purchase intention of hybrid vehicle, where the three (3) factors are acceptability, accessibility and awareness.